ChemInform Abstract: Organocatalytic Enantioselective Synthesis of Tetrahydrofluoren‐9‐ones via Vinylogous Michael Addition/Henry Reaction Cascade of 1, 3‐Indandione‐Derived Pronucleophiles. Issue 27 (16th June 2016) - Moehlmann, Lennart; Chang, Geng‐Hua; Madhusudhan Reddy, G.; Lee, Chia‐Jui; Lin, Wenwei
Abstract: An asymmetric vinylogous Michael addition/Henry cyclization cascade with 1, 3‐indandione derivatives (I), (IV), and (VI) and nitro alkenes affords highly substituted tetrahydrofluorenones.